A randomized controlled trial of a weight loss maintenance program in adults with obesity - Pereira, Vanessa (2024)
Funding Information: This work was sponsored by Farmodietica S.A. The study was also promoted by the CINTESIS@RISE, NOVA Medical School, NOVA University of Lisbon and financed by national funds through FCT Fundacao para a Ciencia e a Technologia, I.P., within the scope of the project \u201CRISE \u2013 LA/P/0053/2020\u201D. The sponsor and funder had no role in the study design and had no role during its execution, analysis, interpretation of the data, or decision to submit the results. Publisher Copyright: © The Author(s), under exclusive licence to Springer Nature Limited 2024.